Wastewater Treatment in Cold Climates - Sletten,Robert S.; Uiga,Ants (1976)
Wasterwater treatment at remote military installations in Alaska presently consists of aerated lagoons and extended aeration package plants. Although performance data for these systems are either very limited or in most cases nonexistent, indications are that most of these systems can not meet secondary effluent criteria as defined by the EPA. Processes for upgrading to meet the new criteria must be as simple as possible to design, build and operate. In particular, the requirements for operation and maintenance should be minimal due to the remote, isolated nature of most of the camps. Processes which appear to be feasible include land application, intermittent filtration, and variations of ponding.